Social network markets: A new definition of the creative industries - Potts, J.; Cunningham, S.; Hartley, John; Ormerod, P. (2008)
We propose a new definition of the creative industries in terms of social network markets. The extant definition of the creative industries is based on an industrial classification that proceeds in terms of the creative nature of inputs and the intellectual property nature of outputs. We propose, instead, a new market-based definition in terms of the extent to which both demand and supply operate in complex social networks. We review and critique the standard creative industries definitions and explain why we believe a market-based social network definition offers analytic advance. We discuss some empirical, analytic and policy implications of this new definition. © 2008 Springer Science+Business Media, LLC.